Comparison of Fermentation and Wines Produced by Inoculation of Hanseniaspora vineae and Saccharomyces cerevisiae - Lleixà, Jessica; Martín, Valentina; Portillo, María del C.; Carrau, Francisco; Beltran, Gemma; Mas, Albert (Frontiers in Microbiology, 2016)
Interest in the use of non-Saccharomyces yeasts in winemaking has been increasing due to their positive contributions to wine quality. The non-Saccharomyces yeast Hanseniaspora vineae is an apiculate yeast that has been associated with the production of wine with good aromatic properties. However, little is known about the fermentation dynamics of H. vineae in natural must and its interaction with autochthonous yeasts. In the present study, we performed semi industrial fermentations of Macabeo and Merlot musts inoculated with either H. vineae or S. cerevisiae. The yeast population dynamics were monitored by plate culturing, qPCR, PCR-DGGE and massive sequencing techniques. The results obtained with these techniques show that H. vineae was able dominate the autochthonous microbiota in Macabeo must but not in Merlot must, which exhibited a larger, more diverse yeast population. The presence of H. vineae throughout most of the Macabeo fermentation resulted in more fruity and flowery wine, as indicated by the chemical analysis of the final wines, which demonstrated a strong presence of phenethyl acetate at concentrations higher than the threshold of perception and approximately 50 times more than that produced in wines fermented with S. cerevisiae. This compound is associated with fruity, floral and honey aromas.